2017
DOI: 10.1016/j.aprim.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Control del asma en pacientes que acuden a consulta de atención primaria en España (estudio ACTIS)

Abstract: Prevalence of poor asthma control among patients attending due to symptoms worsening continues to be very high even in patients who come to renew their prescription. Poor asthma control is associated to high use of resources and high impact on burden of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
2
0
7
Order By: Relevance
“…Despite their heterogeneity, all showed the same tendency toward poor asthma control. In a recent Spanish publication, Calvo et al 19 found poor asthma control (ACT ≤ 20) ranging from 23.4 to 75.6% in 638 asthmatic patients, depending on the patients' medical consultation. On average, almost half of the patients showed poor control.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their heterogeneity, all showed the same tendency toward poor asthma control. In a recent Spanish publication, Calvo et al 19 found poor asthma control (ACT ≤ 20) ranging from 23.4 to 75.6% in 638 asthmatic patients, depending on the patients' medical consultation. On average, almost half of the patients showed poor control.…”
Section: Discussionmentioning
confidence: 99%
“…These issues probably affect the adherence of patients: half of the patients did not take their maintenance medications correctly in the REALISE study11, and 50 percent did not take maintenance medications as prescribed among patients with poor control because they felt it was not necessary. Nearly 50 percent of patients in another study10 believed their asthma was well managed, even though they had extreme and persistent symptoms (19).…”
Section: International Journal Of Medical and Biomedical Studies (Ijmbs)mentioning
confidence: 97%
“…La prueba de X 2 fue empleada para medir asociación, los valores p < 0,05 se consideran significativamente estadísticos. (16) y del 44 % reportado por Alvear et al (Chile) (17) . Respecto a la forma de establecer el control, este fue realizado mediante el ACT, tanto en las investigaciones mencionadas como en este trabajo; sin embargo, a diferencia de los demás, nuestros datos fueron recolectados de las historias clínicas.…”
Section: Análisis Estadísticounclassified
“…Respecto a la forma de establecer el control, este fue realizado mediante el ACT, tanto en las investigaciones mencionadas como en este trabajo; sin embargo, a diferencia de los demás, nuestros datos fueron recolectados de las historias clínicas. La similitud cultural en países latinos quizás sea la causa de la frecuencia de control de asma hallada, sin dejar de considerar el hecho de contar con menor población respecto al estudio realizado en España, el que se aproxima a los 700 pacientes (16) .…”
Section: Análisis Estadísticounclassified